Penerapan Pendekatan Arsitektur Perilaku dalam Children Care Center di Kabupaten Badung, Bali - I Gusti Ngurah Nara Indra Prima Satya; I Putu Hartawan; Anak Agung Gede Raka Gunawarman (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
The high number of parents who are busy with their work, especially mothers who are supposed to be educators and caregivers for their children, has led to the need for facilities that can become a place for children so that later they will receive good, efficient and appropriate care and education. can help their growth and development in the future to become better individuals or individuals. Therefore, a facility that can be a solution to this problem is the Children Care Center facility which if it can accommodate all the needs of early childhood by including care services and pre-school education. With the existence of a Children Care Center public facility that involves children as the main actors, an appropriate architectural approach is needed in order to make the Children Care Center a facility that is responsive to all the needs of early childhood as the main users. The Behavioral Architecture approach is the appropriate approach for the Children Care Center facility, because by applying the Behavioral Architecture approach to this facility, it is hoped that the facility can meet the needs of early childhood for what facilities they need by knowing or studying habits, character, behavior, and patterns of early childhood activities.